The Influence of Perception of Tax System Effectiveness on Compliance of Cibaduyut Shoe SMEs Taxpayers - Rakhmadhani, Vania; Napisah, Lilis Saidah (Fakultas Ekonomi Universitas Garut, 2023)
This study aims to determine the extent of the influence of the perception of tax system effectiveness on the compliance of Cibaduyut shoe SME taxpayers. The research method used in this study is descriptive and verification with a survey method. The data used in this study is primary data obtained by distributing questionnaires to 60 SME taxpayers located in Cibaduyut. In this study, data were obtained from the results of questionnaires distributed to 60 Cibaduyut shoe SME taxpayers. The statistical method used is simple linear regression analysis. The results show that the level of perception of tax system effectiveness has an effect on the compliance of Cibaduyut shoe SME taxpayers.